"Library is my second home" : Library as a multigallery/ Perpustakaan UiTM Puncak Alam - Mokhtar, Norfazira; Ainul Hayati; Ainur Zulaikhahani (Faculty of Art and Design, Universiti Teknologi MARA, 2019)
There are several problem statement for this project. The problem is student always think that library is not interesting place that they wan to go. As a student, they have noot entertainment while study. PTAR library thought full of resources, facilities and activities for UiTM student lack of attention. It lacks the 'feeling' of a second home and a multigallery library.